2023
DOI: 10.1111/jdi.14021
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the COVID‐19 pandemic on the glycemic control in people with diabetes mellitus: A retrospective cohort study

Abstract: Aim To investigate the impact of the COVID‐19 pandemic and its preventive measures on the glycemic and lipid control in people with diabetes mellitus (DM). Materials and methods We conducted this retrospective cohort study from April 2019 to March 2021; we termed the period from April 2019 to March 2020 as the pre‐COVID‐19 period, and the period from April 2020 to March 2021 as the COVID‐19 period, and divided each of these two periods into four quarters. Results In the 1st quarter of the COVID period, when th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 40 publications
0
0
0
Order By: Relevance
“…The observed increase in HbA1c values on a population level as well as on an individual level has been previously reported in multiple studies [13][14][15]. In a systematic review investigating glycemic control in patients with diabetes, a meta-analysis showed an HbA1c increase of 0.14% (−0.13 to 0.40) in persons with T2D, based on eight studies [14].…”
Section: Previous Studiessupporting
confidence: 53%
“…The observed increase in HbA1c values on a population level as well as on an individual level has been previously reported in multiple studies [13][14][15]. In a systematic review investigating glycemic control in patients with diabetes, a meta-analysis showed an HbA1c increase of 0.14% (−0.13 to 0.40) in persons with T2D, based on eight studies [14].…”
Section: Previous Studiessupporting
confidence: 53%
“…Several studies found that the COVID-19 pandemic led to a notable increase in GDM prevalence when using the gold standard diagnostic method. This increase was attributed to exposure to various stressful factors such as lockdowninduced restrictions, heightened anxiety and depression, and alterations in dietary habits 36,[52][53][54] . However, this review suggested that the incidence of GDM appeared to decrease when new screening methods were introduced during the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…Theo nghiên cứu của Kanako Ohkuma, tổng hợp lại nhiều nghiên cứu trước đây về sự tác động của COVID-19 tới hơn 4000 người bệnh ĐTĐ, trung bình HbA1c trước và sau mắc COVID-19 lần lượt là 7.05 ± 0.01% vs. 7.11 ± 0.01%, p <0.001 7 .…”
Section: Bàn Luậnunclassified
“…Ở nghiên cứu của Kanako Ohkuma, tác giả cũng cho thấy các chỉ số mỡ máu có sự thay đổi đáng kể về mặt thống kê, với trung bình Cholesterol trước và sau mắc COVID-19 là 4,78 ± 0.53; 4,79 ± 0.55 và p <0.001 7 .…”
Section: Bàn Luậnunclassified